2014
DOI: 10.1037/neu0000027
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological outcomes in OEF/OIF veterans with self-report of blast exposure: Associations with mental health, but not MTBI.

Abstract: A history of mTBI with or without LOC during deployment does not contribute to objective cognitive impairment in the chronic phase post injury. In contrast, PTSD and depression symptoms are associated with cognitive performance decrements. This finding is thought to reflect at least in part the impact of psychiatric distress on neuropsychological performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
51
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 68 publications
10
51
0
1
Order By: Relevance
“…Future research should further examine the impact of mechanism of injury, and investigators should consider conducting research on blast exposure regardless of MTBI diagnosis due to the potential for misclassification of MTBI status. When examining cognitive outcomes, many researchers adjust for the known confounders of age and education; however, this study and others support the need to include PTSD as a covariate (Verfaellie et al, 2014).…”
Section: Discussionmentioning
confidence: 84%
“…Future research should further examine the impact of mechanism of injury, and investigators should consider conducting research on blast exposure regardless of MTBI diagnosis due to the potential for misclassification of MTBI status. When examining cognitive outcomes, many researchers adjust for the known confounders of age and education; however, this study and others support the need to include PTSD as a covariate (Verfaellie et al, 2014).…”
Section: Discussionmentioning
confidence: 84%
“…This likely reflects overlap in symptoms between the 2 disorders but is also consistent with the proposal that PTSD and depression in the aftermath of trauma are best conceptualized as a single, general response to traumatic stress. 89 In our previous work, 38 we evaluated PTSD and depression in separate models as predictors of cognitive outcome and found that both were significant predictors, although the model fit was better with PTSD as the predictor, hence the focus on PTSD in this study. However, additional mental health variables such as substance use should also be considered in future work.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies examining associations of chronic mTBI and PTSD with neuropsychological outcomes have highlighted PTSD symptoms as a primary contributor to cognitive impairment. [35][36][37][38] Although there is some evidence that sleep duration may moderate the association between PTSD and cognitive function, 32 no study has directly assessed the overlap among PTSD, sleep disturbance, and cognitive outcomes, while taking into account mTBI-comorbidity. Here, we evaluate whether self-reported sleep disturbance mediates the relationship between PTSD and cognitive outcomes.…”
Section: Us Department Of Veterans Affairsmentioning
confidence: 99%
See 2 more Smart Citations